An analysis of the e-learning market in the United Kingdom - Xie, Xiangli (2008)
E-learning has been a rapid growing industry in the last few decades in the United Kingdom. This dissertation examines the UK e-learning market and analyzes the investment opportunities in this industry. The literature review and the research approach are presented. The analysis of the current market situation, future market trend, and possible growth areas is considered. Different influential factors, including political, economic, social, technological, legal, and environmental factors are discussed. The analysis of three investee companies is highlighted. Finally, the study of specialist investors focuses on four venture capital investors. It is concluded that the UK e-learning market will continue to increase in the next few years. The huge investment opportunities in this highly competitive market will attract an increasing number of specialist investors to set foot in this industry. This may be of interest to venture capital or private equity firms, especially those involved in social business investment.